NATIONAL DEFENCE AND SECURITY - Grozdanoska, Natasha (European Scientific Journal, ESJ, 2014)
Safety is a condition in which states consider that there is no danger of a military attack from political coercion or economic compulsion, so it can easily be developed. Security is actually inherent structural element of the state that the present degree of cultural and civilization development requires a modern approach to the solution and organization. When we are talking about national security, usually emphasized that one of the basic functions of the state is to provide a system of relationships from harmful outside influences. National security of a country must not threaten the fundamental values of the national security of all other countries, members of the international community. The politics of national security is a complex and interdependent set of measures, activities, plans and programs undertaken by Republic of Macedonia to protect, maintain and enhance the security of Republic of Macedonia and its citizens, in accordance with available resources and active cooperation with the international community.